The application of the Anti-corruption Law and the State-owned Law: compliance as an overview of the link between the public and the private - Borges de Oliveira, Emerson Ademir (2022)
This article will analyze the application and effectiveness of the Anti-Corruption Law, its regulatory decree and the Law of State-owned Companies against the impact of corruption that affects the public order, aiming to establish as a balancing element the concepts and doctrines linked to the implementation of Compliance Programs. The proposed problematic will address the barriers in relation to the control and inspection systems within the state-owned companies and the conclusion will be given by the provision of resolving hypotheses to institute optimizing business policies within the Public Administration.